Świat jest w nas... Obrazy siebie i wewnętrznego świata w refleksjach początkujących nauczycielek - Barabasz, Grażyna (Kultura-Społeczeństwo-Edukacja, 2023)
The inspiration to create this text, and previously to conduct research among novice teachers (students of preschool and early school pedagogy) about their self-image and personal, inner world, are the words of my supervisor and educator, Professor Stanisław Dylak. The professor began his lectures on pedeutology for pedagogy students with the statement: “The world is within us.” For many, these words became an impulse to reflect on themselves, and for those more committed, also to reflect on their own identity as a teacher. They became a pretext for conversations with oneself, an answer to the question Who am I? What am I like? What kind of teacher do I want to be? These questions become even more important when we realize, referring to our own biographical experiences, that “The Teacher comes close to eternity. He can never tell where his influence ends” (Henry Brooks Adams). This text is an attempt to get to know the inner world of female pedagogy students who are planning to start working as teachers in the coming months or have just started it. The author designed and conducted qualitative research on a group of 12 beginning teachers – students of preschool and early school pedagogy, and in the presented text she presented the images of themselves and “their” world outlined by them. An interpretive approach was used to analyze the obtained data, which allowed for the presentation of a collective picture of the internal world of teachers at the beginning.